Evaluation of conductive polymers as an adsorbent for eradication of As (III) from aqueous solution using inductively coupled plasma optical emission spectroscopy (ICP-OES) - Muhammad Imran Din; Sadia Ata; Ijaz Ul Mohsin; Ata Rasool; Andleeb Andleeb Aziz (International Journal of Science and Engineering, 2014)
The main focused of this research work is the preparation of conductive polymers like polypyrrole, polyaniline and polythiophene and their application as adsorbent materials for the removal of hyper toxic metal As (III) from aqueous solution. The metal ions get attached on the π-electrons at the back bone of polymer that illustrate excellent affinity for metal ions. The adsorption of As (II) ions was carried out on polythiophene due to its redox properties and the stronger interaction between sulfur atoms with arsenic atoms. To attain large surface area and for maximum interaction of As (III) ions with polymers, the particle size of polymers was ranged in nano scale. As the surface area increases with decrease in particle size, the active sites for metal ions also increases. These polymers were characterized by FIIR spectroscopy and SEM analysis. Adsorption isothermal data was examined by two parameters (Langmuir, Freundlich, and Dubinin-Radushkevich) and three parameters Redlich-Petrson, Sips and Toth models. Experimental results showed that based on standard deviation (SD) and Chi square test (χ2) the experimental data was best explained by Freundlich and Toth isotherm. Thermodynamics parameters such as free energy change (ΔG0), enthalpy change (ΔH0) and entropy change (ΔS0) have been calculated respectively, which revealed the spontaneous, endothermic and feasible nature of adsorption process.